2001
DOI: 10.1099/0022-1317-82-5-1157
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus gene polymorphisms in Chinese Hodgkin’s disease cases and healthy donors: identification of three distinct virus variants

Abstract: Epstein-Barr virus (EBV) is associated with several malignancies. Specific EBV gene variants, e.g. the BamHI f configuration, a C-terminal region 30 bp deletion in the latent membrane protein-1 (LMP1) gene (del-LMP) and the loss of an XhoI site in LMP1 (XhoI-loss), are found in Chinese cases of nasopharyngeal carcinoma (NPC), suggesting that EBV sequence variation may be involved in oncogenesis. In order to understand better the epidemiology of these EBV variants, they were studied in virus isolates from EBV-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
7
25
0
3
Order By: Relevance
“…This slight female predilection in NHL may be related to the repeated blood transfusions during deliveries, which carry the risk of viral infections and transmission of chemical carcinogens. 16 In accordance with previous studies 12 HD had male predilection. This finding could be explained by the prevalence EBV infection in males than in females.…”
Section: Discussionsupporting
confidence: 79%
“…This slight female predilection in NHL may be related to the repeated blood transfusions during deliveries, which carry the risk of viral infections and transmission of chemical carcinogens. 16 In accordance with previous studies 12 HD had male predilection. This finding could be explained by the prevalence EBV infection in males than in females.…”
Section: Discussionsupporting
confidence: 79%
“…33 Subsequent to this initial report, numerous LMP1-variants from both nasopharyngeal carcinomas and Hodgkin's lymphomas have been described by various groups. [34][35][36] However, to our knowledge, results published in the literature fail to demonstrate direct associations between any single LMP1-variant and any specific EBV-associated disease. [34][35][36] Based on phylogenetic analysis, Nancy Raab-Traub's group proposed classifing LMP1 natural variants into seven distinct strains, and showed a bias regarding the frequency of some LMP1 strains and nasopharyngeal carcinomas, suggesting a potential selection pressure on these variants during epithelial cell oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] However, to our knowledge, results published in the literature fail to demonstrate direct associations between any single LMP1-variant and any specific EBV-associated disease. [34][35][36] Based on phylogenetic analysis, Nancy Raab-Traub's group proposed classifing LMP1 natural variants into seven distinct strains, and showed a bias regarding the frequency of some LMP1 strains and nasopharyngeal carcinomas, suggesting a potential selection pressure on these variants during epithelial cell oncogenesis. 24 Our previous analysis of the LMP1 polymorphism in both Reed-Sternberg cells and normal Blymphocytes from Hodgkin's lymphomas clearly suggested an intra-host diversity for the two viral strains from a common viral ancestor and showed that LMP1-variants in tumor cells are highly mutated when compared to LMP1-variants from healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…и дополнительно 26 аминокислотных замен [1]. Доказано, что функционально LMP1-Сао по сравнению с LMP1-В95.8 обладает более вы-раженным трансформирующим потенциалом in vitro [19], а также повышенной туморогенно-стью, сниженной иммуногенностью и усилен-ной сигнальной активностью [1,15,22]. Пока-зано также, что нуклеотидные замены в генах, кодирующих различные варианты LMP1, как правило, расположены в областях, контролиру-ющих стадии транскрипции или трансляции.…”
Section: Introductionunclassified
“…Пока-зано также, что нуклеотидные замены в генах, кодирующих различные варианты LMP1, как правило, расположены в областях, контролиру-ющих стадии транскрипции или трансляции. В составе белка -это аминокислоты, которые влияют на функциональную активность, им-муногенность, время полужизни или трансфор-мирующий потенциал LMP1 [15,22]. Актива-ция LMP1 целого ряда транскрипционных фак-торов (NF-κB, AP-1, STAT) изменяет профиль внутриклеточной активности ряда сигнальных путей [20].…”
Section: Introductionunclassified